1988
DOI: 10.1055/s-2007-1018187
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Variant Insertions of the Ligamentum Teres Hepatis in the Cruveilhier-Baumgarten Syndrome

Abstract: Within the framework of a prospective study, we were able to establish that in 50 per cent of 220 patients submitted to laparoscopy, the ligamentum teres hepatis did not run from the porta hepatis directly to the umbilicus, but to a point of insertion craniad to the umbilicus in the median line of the anterior abdominal wall. As a rule, this topographic variant has no clinical relevance. It is, however, of importance in patients with cirrhosis of the liver and portocaval collateral channels. In our group, 25 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The ligament has also been reported to reach the umbilicus and a supra-umbilical site in 50% and 49% of cases, respectively 4. However, the present study has shown that LTH is frequently divided into several branches before it reached the UR, which is consistent with a report of the lower third of the umbilical vein undergoing breakdown and completely dividing into vascular fibro-elastic strands in early childhood 7.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ligament has also been reported to reach the umbilicus and a supra-umbilical site in 50% and 49% of cases, respectively 4. However, the present study has shown that LTH is frequently divided into several branches before it reached the UR, which is consistent with a report of the lower third of the umbilical vein undergoing breakdown and completely dividing into vascular fibro-elastic strands in early childhood 7.…”
Section: Discussionsupporting
confidence: 92%
“…2). The discrepancy among these studies might be due to inter-racial variations or different observation methods: the observations were made with the naked eye,3 laparoscopically without removing the peritoneum in patients with Cruveilhier-Baumgarten syndrome,4 and under a surgical microscope (present study) - only our observation method is sufficient to allow the slender terminal branches deriving from the ligament to be traced.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this review, bleeding from the abdominal wall and umbilical veins caused by the trocar (8 deaths) and complications following liver biopsy, with bleeding, bile leakage and bile peritonitis (17 deaths), posed the highest risk [15] . Catastrophic bleeding from large caliber vessels in the abdominal wall may be avoided by pre-laparoscopic US with high-frequency and high-resolution linear scanners and with the aid of duplex sonography; laparoscopists can use these methods to reduce potential injury to these vessels by selecting the trocar as the point of entry [16] . A 5 mm caliber mini-laparoscope is used in our clinical practice.…”
Section: Safety Of Mini-laparoscopymentioning
confidence: 99%
“…23,24 However, this is the first report in which sonography has documented such a long and unusual course for a PUV, down to its communication with the right EIV, in a case of hepatic venous outflow obstruction (as described for patient 1). Identifying such an extension is very important to avoid causing hemorrhage, which could be fatal, during any invasive investigative technique (eg, laparoscopy 25 ) or surgical procedure (eg, appendectomy) in this area. Generally, the hemodynamic role of a patent PUV varies from being a hepatofugal pathway in cases of intrahepatic portal hypertension to a hepatopetal pathway in cases of extrahepatic PV obstruction.…”
Section: Discussionmentioning
confidence: 99%